2022
DOI: 10.1002/jmri.28177
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Understanding of the Complex Role of Venous Sinus Stenosis in Idiopathic Intracranial Hypertension

Abstract: Idiopathic intracranial hypertension (IIH) is a disorder characterized by elevated intracranial pressure (ICP) that predominantly affects young obese women. IIH is a diagnosis of exclusion. That is, if increased ICP is suspected, magnetic resonance imaging and magnetic resonance venography of the brain are recommended to exclude secondary causes. Imaging findings, such as empty sella, orbital findings, meningocele, and encephalocele, are not diagnostic of ICP, nor does their absence exclude ICP either. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
3
4
0
Order By: Relevance
“…In our study, transverse-sigmoid stenosis was found to be severe in both groups. As in many other studies, these results highlight the importance of venous stenosis in the patho-mechanism of IIH [ 17 , 21 , 22 ]. In some studies, obesity is mentioned as a possible trigger or ameliorating factor for venous stenosis [ 21 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, transverse-sigmoid stenosis was found to be severe in both groups. As in many other studies, these results highlight the importance of venous stenosis in the patho-mechanism of IIH [ 17 , 21 , 22 ]. In some studies, obesity is mentioned as a possible trigger or ameliorating factor for venous stenosis [ 21 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…As in many other studies, these results highlight the importance of venous stenosis in the patho-mechanism of IIH [ 17 , 21 , 22 ]. In some studies, obesity is mentioned as a possible trigger or ameliorating factor for venous stenosis [ 21 , 23 , 24 ]. However, we found the non-obese population to have a very high degree of venous stenosis, suggesting that venous stenosis may not necessarily be caused or influenced by obesity.…”
Section: Discussionsupporting
confidence: 88%
“…However, to date, a technique does not exist to measure the VTT. It is plausible that our ability to measure this parameter will open new avenues of research in vessel properties (e.g., dilation and tortuosity 23 ) and diseases (e.g., cerebral small vessel disease, 9,21 stroke, 25 idiopathic intracranial hypertension, 50 malformation of venous vasculature 23 ). Another MRI technique, reverse perfusion imaging, was recently proposed to probe venous physiology 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors form a vicious circle. 14 ) Extrinsic stenosis of the venous sinus is not considered an independent cause of IIH. 14 ) Similarly, in the present case, the venous sinus obstruction is related to intrinsic and extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
“… 14 ) Extrinsic stenosis of the venous sinus is not considered an independent cause of IIH. 14 ) Similarly, in the present case, the venous sinus obstruction is related to intrinsic and extrinsic factors. Venous sinus stenting can stop this vicious circle, but it must be ineffective to the primary cause.…”
Section: Discussionmentioning
confidence: 99%